x= -1
2006-12-27 15:37:12
·
answer #1
·
answered by Anonymous
·
4⤊
0⤋
2x - 2 = 8x + 4
2x - 2 - 2x = 8x + 4 - 2x
- 2 = 6x + 4
- 1 - 4 = 6x + 4 - 4
- 6 = 6 x
- 6/6 = 6x/6
- 1 = x
The answer is x = - 1
Insert the x value into the equation
- - - - - - - - - - - - - - - - - - - - - - -
2x - 2 = 8x + 4
2(- 1) - 2 = 8(- 1) + 4
- 2 - 2 = - 8 + 4
- 4 = - 4
- - - - - - - - s-
2006-12-28 06:52:23
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
Just rearrange the equation so all the term in x are on the left hand side and the constants on the right so - you do this by adding (or subtraction the same thing on both sides as this has no effect on the equality:
2x - 2 = 8x + 4 =>
2x - 8x = 4 + 2 (you get here by subtracting 8x from both sides, and adding 2 to both sides)
Which reduces to:
-6x = 6
No divide both sides by 6 so
-x = 1
And then both sides by -1
So x = -1 and that is the answer
Now always check you answer by substituting it back into the equation
so the left hand side is
2*(-1) -2 = -2 -2 = -4
and the right hand side
8*(-1) + 4 = -8 + 4 = -4
So both sides equal and the answer is indeed correct
2006-12-27 23:41:11
·
answer #3
·
answered by Andy 2
·
3⤊
1⤋
2x - 2 = 8x + 4
2x - 8x = 4 + 2 = 6
-6x = 6
x = -1
2006-12-28 00:08:23
·
answer #4
·
answered by Srinivas c 2
·
0⤊
0⤋
2x-2 = 8x +4
2x-2 –2x -4 = 8x+4 –4 – 2x
-6 = 6x
-6/6 = 6x/6
-1= x
2006-12-27 23:45:17
·
answer #5
·
answered by Anonymous
·
1⤊
1⤋
Firstly, you want to isolate the variable (x) and it's coefficienct on one side of the equal sign. In order to do that, you subtract 8x or 2x from both sides of the equation (either way, it doesn't matter).
Since positive numbers are peachy for now, we'll subtract 2x from both sides to get:
-2 = 6x +4
Now, we need to get rid of one of the terms on the right side (4). To do this, we need to subtract 4 from both sides of the equation. Subtracting 4 is the same as adding negative 4, so we add negative 4 to both sides and we get:
-6 = 6x
Now, we need to get rid of the coefficient (6). To do this, you divide both sides by 6 (6x/6 -- the 6's will cancel out and you are left with just an x). On the other side, it is -6/6. Leaving you with:
x = -1
To check, plug -1 in for where you see x:
2(-1) - 2 = 8(-1) + 4
-2 - 2 = -8 + 4
-4 = -4 ... -4 does, in fact, equal itself.
2006-12-27 23:43:35
·
answer #6
·
answered by Novy 5
·
1⤊
1⤋
2x - 2 = 8x + 4
2x - 8x = 4 + 2
-6x = 6
x = -1
Solution: {x elements of R | x = -1}
<>>
2006-12-28 20:57:06
·
answer #7
·
answered by aeiou 7
·
0⤊
0⤋
combine the common factors....
worked out:
2x-2= 8x+4
2x-8x= 4+2
-6x=6
x=-1
2006-12-28 01:30:26
·
answer #8
·
answered by kowalley 5
·
0⤊
0⤋
2x - 2 = 8x + 4
First add 2 to both sides.
2x = 8x + 6
Then subtract 8x from each side.
-6x = 6
Divide each side by -6.
x = -1
Plug in the answer; it works!
2006-12-27 23:55:50
·
answer #9
·
answered by Anonymous :) 5
·
0⤊
0⤋
x= -1
2006-12-27 23:39:56
·
answer #10
·
answered by joshl898 1
·
3⤊
1⤋